AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN SPEAKING ENGLISH - Della Puspita Sari; Isna Humaera; Ririn Syahriani (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2023)
The purpose of this study is to find out the causes of students' difficulties in speaking English. This research uses descriptive quantitative method. In collecting data, the researcher used a closed questionnaire and also a Liker scale to determine the factors that cause students' difficulties in speaking. Data collection was carried out by distributing questionnaires to 30 students of class XI IPS. The results of this study indicate that the inhibiting factors, having nothing to say, the lack of participants and the use of the mother tongue can be a source of student difficulties. From these four aspects, the results showed that 72.40% of students experienced inhibition, 60% could nothing to say, 60.93% low participations and 64.4% used their mother tongue. It can be concluded that of the four factors there is one factor that shows high presentation value, namely the obstacle where most students have obstacles in speaking English so they find it difficult to speak.